2013
DOI: 10.1007/s00128-012-0957-4
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Distribution in a Mangrove Tidal Creek Affected by Intensive Shrimp Farming

Abstract: In this study, the Hg distributions in water and sediments from a mangrove creek that receives intensive shrimp farming effluents were determined. The average dissolved and particulate Hg concentrations in the water varied from 3.1 to 9.2 ng L(-1) and from 4.4 to 9.4 ng L(-1), respectively. However, the Hg concentrations in the suspended particulate matter and the bottom sediments varied from 95.4 to 115.7 ng g(-1) and from 1.6 to 10.3 ng g(-1), respectively. A Ward quadratic distance cluster analysis based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
10
1
1
Order By: Relevance
“…In an attempt to determine the distribution of Hg in creek waters receiving effluents from shrimp farms in the lower Jaguaribe River, Costa et al (2013) found lower Hg-D concentrations (3.1-9.2 ng l −1 ) but higher Hg-P (4.4-9.4 ng l −1 ) levels than were found in the present study, likely due to the much higher TSS content in the creek waters compared with the Castanhão Reservoir. Lacerda et al (2013) also found lower concentrations of Hg-D in the Jaguaribe River proper (0.3-3.8 ng l −1 ) and noted slightly higher Hg concentrations in the TSS (13.1-129.8 ng g −1 ).…”
Section: Estimated An Emissioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In an attempt to determine the distribution of Hg in creek waters receiving effluents from shrimp farms in the lower Jaguaribe River, Costa et al (2013) found lower Hg-D concentrations (3.1-9.2 ng l −1 ) but higher Hg-P (4.4-9.4 ng l −1 ) levels than were found in the present study, likely due to the much higher TSS content in the creek waters compared with the Castanhão Reservoir. Lacerda et al (2013) also found lower concentrations of Hg-D in the Jaguaribe River proper (0.3-3.8 ng l −1 ) and noted slightly higher Hg concentrations in the TSS (13.1-129.8 ng g −1 ).…”
Section: Estimated An Emissioncontrasting
confidence: 79%
“…These results suggest that all Hg that enters the farm area via fish farming practices may accumulate in the farm's sediments. Lacerda et al (2009) and Costa et al (2013) also reported that the majority of Cu emitted in the lower Jaguaribe River as a result of aquafeed used in shrimp farming does so in the bottom sediments.…”
Section: Estimated An Emissionmentioning
confidence: 90%
“…Concerning Hg, the average concentrations (μg g −1 dw) of Hg in shrimp ranged from 0.16 ± 0.04 (Pemalang) to 1.35 ± 0.89 (Brebes). The Hg source may have originated from the drainage basin (industrial, agricultural, and domestic effluents), where Hg is trapped and accumulates in a mangrove tidal creek, which may be a potential source of contamination in adjacent aquaculture sites (Costa et al 2013), or the source may have originated from the shrimp farms because of the large amounts of feed applied during breeding. Lacerda et al (2011) estimated an EF from intensive shrimp farming of 83.5 mg Hg ha…”
Section: Occurrence Of Metals In the Shrimpmentioning
confidence: 99%
“…Mercury in coastal wetland and estuarine sediments is of significant interest due to its presence from often unambiguous historical industrial sources and its pervasive accumulation through food webs (Cotin et al, 2011; Elbaz‐Poulichet et al, 2011; Kongchum et al, 2006; Mitchell & Gilmour, 2008; O'Driscoll et al, 2011). Mercury is of particular biogeochemical and toxicological interest in mangrove–coral and human ecosystems due to distinct food‐web interactions (high biomagnification) and chronic health risks associated with the consumption of reef fish (M. F. M. Costa et al, 2012; Guzmán & García, 2002) and mangrove areas converted to aquaculture (B. Costa et al, 2013; Lacerda et al, 2011). Understanding long‐term anthropogenic and natural Hg cycling with contemporary sediment accumulation dynamics is also important, especially in relation to future remobilisation of colonial and legacy industrial Hg inputs to coastal zones (Fitzgerald et al, 2018; O'Shea et al, 2018; Rúa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%